The perceived role of key stakeholders' involvement in sustainable tourism development - Kim, Kyoung Bae (2013)
This thesis considers how to improve levels of understanding of different stakeholders' perspectives and their involvement in sustainable tourism development. Jeju Island has been relying on tourism to support the economy and has consequently emerged as the most developed tourist destination in Korea, launched as a result of growth-oriented regional policies of the central and local government over the last thirty years. For sustainable tourism to be successful, it requires the stakeholders' support in the community to develop tourism in a sustainable manner. Therefore, this study focuses on building knowledge about stakeholder perceptions of government led tourism development by investigating stakeholder groups. Also, for this research aim, a qualitative approach was applied, interviews are used to take information for a specific purpose, and this research used semi-structured interviews to obtain relevant information from 42 key informants. For analysis of the qualitative data from the key informants, this study employed Grounded Theory (GT) as a tool for data analysis and interpretation.